Restricting Choices: Decision Making, the Market Society, and the Forgotten Entrepreneur - Wolcott, Gregory (Journal of business ethics, 2019)
Basing their claims on findings in the behavioral sciences that illuminate cognitive deficiencies, scholars spanning multiple disciplines argue that certain features of free market capitalist societies threaten human wellbeing, especially insofar as such societies are marked by a proliferation of consumer choices and incessant demands on decision making. This paper thus attempts three things. First, it outlines the criticisms of the expansive freedoms found in free market societies, based on those findings, in order to provide a reliable overview of the shape of the critics’ concerns. Second, it surveys typical objections to these critics’ concerns, while also taking note of actual and anticipated counter-responses, in order to demonstrate why the debate about the value of those freedoms is not settled by those objections. Third, it argues that one objection remains that demands further debate and consideration before the critics’ choice restrictions should materialize. Namely, since there is solid evidence that entrepreneurship contributes to overall happy and healthy societies, and since the benefits of entrepreneurship are best realized in the types of societies marked by more expansive freedoms than the critics would countenance, the critics, who are concerned with general wellbeing, ought to consider the impact of their choice-restricting proposals on entrepreneurship. This paper does not claim that these critics offer baseless concerns about various threats to our wellbeing that arise from ample exercises of liberty, but it does argue that recognizing the role that entrepreneurship plays in fostering such wellbeing severely dampens the force of their implications for liberty.